Efecto de la fertilización orgánica en la producción de forraje verde y calidad nutricional de la Avena sativa L en condiciones de campo en la Quinta Experimental Punzara. - Condor Buri, Michael Vinicio (2024)
Cattle raising is a fundamental pillar of Ecuador's agricultural sector because of its dynamism in the rural economy; pasture represents the most important source of livestock feed and is low cost. Fodder oats are a high yielding crop with a green fodder production of 30 to 40 t/ha of good nutritional quality, being an important species for the continuously growing livestock sector. The present study evaluated the forage production and nutritional quality of Avena sativa L with organic fertilization, established at the Experimental Farm “Punzara” of the National University of Loja, under a Block Design Completely Randomized (DBCA) with 4 treatments and 3 replications. T1 (control), T2 (nutrisane organic fertilizer), T3 (algasoil organic fertilizer) and T4 (multimix organic fertilizer). The variables evaluated were plant height, tillering, leaf length, aerial coverage, number of leaves, recorded every 10 days from germination, green matter and dry matter production were evaluated at 90 days after sowing (DDS), as well as nutritional quality variables. ANOVA statistical analyses were performed in the InfoStat program. The grass that reached the greatest height with 78.71 cm was T4 and the lowest height was reached by T1 with 66.29 cm at 83 DDS. Yield variables did not show statistically significant differences, but in general T2 and T3 predominated. The best MV production was obtained with algasoil fertilizer 36 086, 04 kg ha-1 per cutting, in relation to the highest content in nutritional value were T2 and T3.